2013
DOI: 10.1186/cc12548
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol levels and neuropsychiatric diagnosis as markers of postoperative delirium: a prospective cohort study

Abstract: IntroductionThe pathophysiology of delirium after cardiac surgery is largely unknown. The purpose of this study was to investigate whether increased concentration of preoperative and postoperative plasma cortisol predicts the development of delirium after coronary artery bypass graft surgery. A second aim was to assess whether the association between cortisol and delirium is stress related or mediated by other pathologies, such as major depressive disorder (MDD) or cognitive impairment.MethodsThe patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 29 publications
2
97
1
3
Order By: Relevance
“…18 It has been found that alterations in the endocrine response to surgery can influence the risk of developing POCD. Higher cortisol levels postoperatively have been shown to be associated with a higher chance of developing POCD, 19 along with suppression of the growth hormone axis. 20 Increased presence of proinflammatory cytokines associated with the surgical stressinduced immune response, such as interleukin (IL)-6, IL-1b, 21 and tumor necrosis factor-alpha, 22 has been shown within the hippocampus postoperatively and is associated with the development of POCD in murine models.…”
Section: Surgical Stress and The Brainmentioning
confidence: 98%
“…18 It has been found that alterations in the endocrine response to surgery can influence the risk of developing POCD. Higher cortisol levels postoperatively have been shown to be associated with a higher chance of developing POCD, 19 along with suppression of the growth hormone axis. 20 Increased presence of proinflammatory cytokines associated with the surgical stressinduced immune response, such as interleukin (IL)-6, IL-1b, 21 and tumor necrosis factor-alpha, 22 has been shown within the hippocampus postoperatively and is associated with the development of POCD in murine models.…”
Section: Surgical Stress and The Brainmentioning
confidence: 98%
“…Moreover, cortisol has been implicated as a potential biomarker for AD in the Australian Imaging Biomarker and Lifestyle Study [54]. Cortisol levels are potentially of a similar importance in delirium; raised levels may play a role in the development of delirium, with the further suggestion that cortisol may be an appropriate biomarker for postoperative delirium [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Ethics Committee of the Medical University of Lodz, Poland, and was performed in accordance with the ethical standards of the Declaration of Helsinki. The subjects included in this study have been previously reported in a paper regarding the role of cortisol in delirium development [36]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to stress is a key factor in the precipitation of symptoms and in subsequent exacerbation of symptoms (Nuechterlein et al, 1992;Miller et al, 2001;Dawson et al, 2010;Cerejeira et al, 2013;Kazmierski et al, 2013), and chronic stress-induced alterations of prefrontal cortical function have been suggested to be associated with the precipitation and exacerbation of these symptoms (Mizoguchi et al, 2000;Cerqueira et al, 2007;Arnsten, 2011). On the other hand, the main approach for treatment of these symptoms involves the use of atypical and typical antipsychotics (e.g., olanzapine and haloperidol).…”
Section: Introductionmentioning
confidence: 97%